EL BaRet: Aplikasi Game Edukasi Matematika untuk Siswa Kelas X SMA Berbasis Android - Efendi, Alvin Junio Ilham; Sugiyanto, Sigit (Jurnal Pendidikan, 2024)
The ease and affordability of technology means that various groups of Indonesian people are familiar with using the internet, especially high school students. Unfortunately, this hurts their academic grades. Dependence on smartphones and online games makes students lazy about studying and difficult to understand lessons. This research aims to combine technological advances to help students become more enthusiastic and easily understand the subject matter. By using Construct 3 and the ADDI method, an educational game application called EL BaRet was created which helps class X high school students in Mathematics lessons on Exponents, Logarithms, Lines and Series. Black box testing and feasibility testing have been carried out with 92% feasibility for the EL BaRet educational game.